2021
DOI: 10.3390/biom11060777
|View full text |Cite
|
Sign up to set email alerts
|

Oximes: Novel Therapeutics with Anticancer and Anti-Inflammatory Potential

Abstract: Oximes have been studied for decades because of their significant roles as acetylcholinesterase reactivators. Over the last twenty years, a large number of oximes have been reported with useful pharmaceutical properties, including compounds with antibacterial, anticancer, anti-arthritis, and anti-stroke activities. Many oximes are kinase inhibitors and have been shown to inhibit over 40 different kinases, including AMP-activated protein kinase (AMPK), phosphatidylinositol 3-kinase (PI3K), cyclin-dependent kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 219 publications
(295 reference statements)
0
37
0
Order By: Relevance
“…In general, flat ring structures have been identified as kinase-specific privileged structures; i.e., compounds containing these fragments are enriched for kinase targets, compared with other target classes ( Posy et al, 2011 ). Thus, although oxime side groups may contribute important interactions in the JNK binding site ( Schepetkin et al, 2012 ; Schepetkin et al, 2015 ; Schepetkin et al, 2019 ; Liakhov et al, 2021 ; Schepetkin et al, 2021 ), the tetracyclic nucleus seems to be responsible for proper ligand positioning. Docking experiments performed in the present study and in our previous work ( Schepetkin et al, 2019 ) show that the tryptanthrin nucleus stipulates good complementarity of the ligands to the JNK1-3 binding sites with similar orientations of the tetracyclic moiety.…”
Section: Resultsmentioning
confidence: 99%
“…In general, flat ring structures have been identified as kinase-specific privileged structures; i.e., compounds containing these fragments are enriched for kinase targets, compared with other target classes ( Posy et al, 2011 ). Thus, although oxime side groups may contribute important interactions in the JNK binding site ( Schepetkin et al, 2012 ; Schepetkin et al, 2015 ; Schepetkin et al, 2019 ; Liakhov et al, 2021 ; Schepetkin et al, 2021 ), the tetracyclic nucleus seems to be responsible for proper ligand positioning. Docking experiments performed in the present study and in our previous work ( Schepetkin et al, 2019 ) show that the tryptanthrin nucleus stipulates good complementarity of the ligands to the JNK1-3 binding sites with similar orientations of the tetracyclic moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies demonstrated that L-NAME did not reduce the relaxation effect of oxime derivatives, but inhibitors of soluble guanylyl-cyclase did [ 21 ]. This finding suggests that oxime–1 could be a potential bioactive molecule in an injured vascular endothelium [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although somewhat forgotten, oximes have been reported to have a vasodilator effect in the presence and absence of vascular endothelium on isolated blood vessels [ 21 ]. In recent years, oximes have gained great interest because of the ease of synthesis from carbonyl compounds, aldehydes, and ketones [ 22 ], and their enormous potential biological activity [ 23 ], especially in their roles such as being donors of nitric oxide [ 24 ], as well as potential β1 and β2 adrenergic receptor antagonists, which might be useful for the treatment of arrhythmia and pulmonary arterial hypertension [ 25 ]. In the search for new derivatives of natural products with potential cardiovascular properties, we have prepared a new oxime (not reported in the scientific literature) from the natural compound 4-hydroxy-3-(3-methyl-2-butenyl) acetophenone.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of these various substituent imidazo[1,2- b ]pyridazine compounds on AChE activity has not been reported. Incidentally, several of these kinases are also inhibited by oxime compounds, which have been reported to have anticancer activities but are better known as AChE reactivators [ 74 ]. It must, however, be noted that the inhibition of kinases by oxime compounds is independent of its activity as an AChE reactivator, which refers to its ability to reverse the action of organophosphates on the enzyme [ 75 ].…”
Section: Discussionmentioning
confidence: 99%